Electrochemical attributes of water from Cerrado wetlands (Veredas), Triângulo Mineiro region, Brazil (Revista Ciência Agronômica, 2023)
Veredas are wetlands typically found in the Brazilian Cerrado playing important environmental functions.The hydromorphic conditions control important processes and reactions occurring in these environments. The objective ofthis study was to assess the pH, redox potential (Eh), and electrolytic conductivity (EC) of water from five veredas locatedin the Triângulo Mineiro region, nearby Uberlândia and Uberaba, Minas Gerais State, Brazil. The pH and EC of watersamples (in triplicate) collected in different positions (upper, middle and bottom) of the selected wetlands were monitoredmonthly from September 2014 to September 2015. Eh was monitored in an incubation experiment using soil samples fromthe superficial layer (0-20 cm) and subsurface layer (40-70 cm) of the middle position of two of the selected veredas. Ingeneral, pH ranged from 3.4 to 6.5 throughout the year. For EC, the values ranged from 1.0 to 67.0 μS cm-1. Most of theyear, pH was between 4.2 and 5.1 and EC was around 9.0 μS cm-1. Under laboratory conditions, Eh decreased from oxidicconditions to suboxidic (reduced) conditions. There were no significant differences between the wetlands and soil layersregarding the variation of Eh.